Senam Anti Hipertensi Sebagai Upaya Penatalaksanaan Non Farmakologis Pada Lansia dengan Hipertensi - Dwi Nur Anggraeni; Faihatul Miskiyah; Sri Mariani Priyanti (LPPM STIKES Madani, 2022)
Hypertension is one of the non-communicable diseases that continues to increase from year to year. The highest prevalence of hypertension sufferers at the age of 55-64 years (55.2%), 65-74 years (63.2%) and >75 years (69.5%) in Indonesia. One of the causes of the incidence of hypertension is a lack of knowledge about the management of hypertension. Management of hypertension can be done pharmacologically and non-pharmacologically by changing lifestyle. One way to change your lifestyle is to do physical activity. A physical activity that can be done in patients with hypertension is anti-hypertensive exercise. This community service aims to provide knowledge, increase awareness and measure blood pressure reduction in the elderly regarding non-pharmacological management of the elderly with hypertension. An anti-hypertension exercise demo was given to the elderly people carried out on May 14, 2022 in Kradenan. The results of this activity were blood pressure before giving anti-hypertensive exercise mostly as much as 76% and blood pressure after giving anti-hypertensive exercise mostly became pre-hypertension as much as 54%, and normal as much as 24%. Giving anti-hypertensive exercise can be used as a non-pharmacological treatment for the elderly by doing anti-hypertensive exercise. The elderly who have prehypertension or hypertension is expected to apply anti-hypertensive exercise 2 times a week to prevent stroke.